Decolonizing African history: Authenticité, cosmopolitanism and knowledge production in Zaire, 1971–1975. Issue 2 (3rd April 2022) - Henriet, Benoît
ABSTRACT: This article analyses the social and intellectual dynamisms of the Lubumbashi campus of the Université Nationale du Zaïre in the 1970s. It first highlights how Lubumbashi scholars participated in an early post-colonial attempt to radically transform the university's teaching, research and operations, at the crossroads of intellectual decolonization and cosmopolitanism. These efforts both overlapped and clashed with the official Zairian policy of Authenticité, a politically tinged reappraisal of the country's precolonial past. The article contributes to our limited knowledge of everyday life under Mobutu and of vernacular experiences of Authenticité, while highlighting Lubumbashi as an important node in the post-independence intellectual networks.